A systematic review of human pathogens carried by the housefly (Musca domestica L.) - Faham Khamesipour; Kamran Bagheri Lankarani; Behnam Honarvar; Tebit Emmanuel Kwenti (BMC, 2018)
Abstract Background The synanthropic house fly, Musca domestica (Diptera: Muscidae), is a mechanical vector of pathogens (bacteria, fungi, viruses, and parasites), some of which cause serious diseases in humans and domestic animals. In the present study, a systematic review was done on the types and prevalence of human pathogens carried by the house fly. Methods Major health-related electronic databases including PubMed, PubMed Central, Google Scholar, and Science Direct were searched (Last update 31/11/2017) for relevant literature on pathogens that have been isolated from the house fly. Results Of the 1718 titles produced by bibliographic search, 99 were included in the review. Among the titles included, 69, 15, 3, 4, 1 and 7 described bacterial, fungi, bacteria+fungi, parasites, parasite+bacteria, and viral pathogens, respectively. Most of the house flies were captured in/around human habitation and animal farms. Pathogens were frequently isolated from body surfaces of the flies. Over 130 pathogens, predominantly bacteria (including some serious and life-threatening species) were identified from the house flies. Numerous publications also reported antimicrobial resistant bacteria and fungi isolated from house flies. Conclusions This review showed that house flies carry a large number of pathogens which can cause serious infections in humans and animals. More studies are needed to identify new pathogens carried by the house fly.